MACROPHAGE IRON CONTENT AND EXACERBATIONS OF COPD - Ho, Terence (My University, 2019)
Background: Many COPD patients have recurrent exacerbations due to infection, but there are no valid predictors of this phenotype. Previously an observational study showed that higher iron content in sputum macrophages was associated with infectious exacerbations. Objectives: The thesis aimed to assess the mechanisms of pulmonary macrophage iron sequestration, test the effect of macrophage iron-loading on bacterial uptake and killing, and prospectively determine if sputum hemosiderin index can predict infectious exacerbations of COPD. Methods: Intracellular iron was measured directly and indirectly in cell-line-derived and isolated sputum macrophages after treatment with exogenous IL-6, hepcidin or heat-inactivated H.influenzae. Bacterial uptake and killing were compared in both types of macrophages, in the presence or absence of iron-loading. A prospective cohort of COPD patients had their sputum hemosiderin index measured at baseline and were monitored for 1-year for infectious exacerbations requiring admission to hospital. Results: For pulmonary iron sequestration, IL-6 appears important, but the role of hepcidin is not clear. Iron-loading reduced the uptake of COPD-relevant organisms by almost one-third in cell-line-derived macrophage, and there was a near-significant linear relationship between sputum hemosiderin index and killing of H.influenzae (p=0.075). In terms of infective exacerbations, FEV1 had predictive utility (beta=-0.051, p=0.017) while a positive trend for sputum hemosiderin index (beta=0.035, p=0.051) suggests that this biomarker has clinical promise. Conclusion: Through in vitro experiments and cohort data, we have established a framework suggesting that excess iron in pulmonary macrophage may contribute to recurrent bacterial airway infection in COPD. IL-6 appears to contribute to sputum macrophage iron sequestration, which subsequently may lead to immune cell dysfunction and ultimately result in an increased frequency of infective exacerbation.
Keywords: COPD; Macrophage; Iron Overload